(untitled) (Journal of Rashid Latif Medical College, 2024)
Objective: One of the most significant innovations in education during the last forty years is problem-based learning (PBL). In terms of the learning outcomes (such as knowledge, attitude, and skills) obtained from both approaches, the study's goal was to compare medical students' preferences for PBL versus regular lectures. Methods: In 2023, Fatima Jinnah Medical University’s medical students enrolled in the hybrid curriculum (PBL and traditional lectures) participated in a cross-sectional study. A self-administered, pre-constructed, validated, confidentially anonymous questionnaire was used to collect the data. The views of students of PBL and regular lectures were assessed through asking them to rate 20 statements on both forms of instruction on a five-point Likert scale. Software used for the analysis and descriptive statistics was SPSS, version 21 (SPSS Inc., Chicago, Ill., USA). Results: PBL was preferred by learners over traditional lectures because it allowed them to better connect their understanding of basic and clinical sciences (t test=10.16, P<.001). Regarding the quantity of fundamental information recalled using both approaches, there was, however, no statistically significant difference (P>.05. PBL was chosen by students over lectures in terms of improved learning attitudes, skills, outcomes for the future, and learning satisfaction (P<.05). PBL encourages learning more than lectures do (P<.05.05). According to the students, there was a highly significant difference (t test=20.9, P<.001) between the mean total skill gained by PBL (47.20 [10.68]) and lectures (33.01 [9.97]). Conclusions: Students preferred PBL more to traditional lectures for improving most of learning outcome domains, especially, learning attitudes and skills. Keywords: Problem-based learning, Traditional Lectures, Medical Students